2011
DOI: 10.1097/brs.0b013e318204f7a2
|View full text |Cite
|
Sign up to set email alerts
|

Patientsʼ Own Accounts of Sciatica

Abstract: STUDY DESIGN.: Longitudinal qualitative interview study, nested within a back pain cohort study. OBJECTIVE.: Enhance the understanding of patients' own perspectives on living with sciatica to inform improvements in care and treatment outcomes. SUMMARY OF BACKGROUND DATA.: Reports of patients' own accounts of sciatica and its impact on daily life are still scarce. Research on back pain has shown that it is important to understand how people live with pain and how they perceive interactions with health care prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
7
34
1
Order By: Relevance
“…Stage 1 requires the respondents to list up to five important areas of life affected by their LBP. This is facilitated by the provision of a 'trigger list' generated for the target condition: 134 a 17-item trigger list was created, informed by qualitative evidence of the impact of LBP, 63,64,140,141 items included in widely used LBP-specific measures 63,65 and recent application of the PGI in a Norwegian LBP population 113 (Box 9).…”
Section: Patient Generated Indexmentioning
confidence: 99%
“…Stage 1 requires the respondents to list up to five important areas of life affected by their LBP. This is facilitated by the provision of a 'trigger list' generated for the target condition: 134 a 17-item trigger list was created, informed by qualitative evidence of the impact of LBP, 63,64,140,141 items included in widely used LBP-specific measures 63,65 and recent application of the PGI in a Norwegian LBP population 113 (Box 9).…”
Section: Patient Generated Indexmentioning
confidence: 99%
“…Qualitative research has indicated that LBP patients search and try to determine objective reasons for their pain [28,29]. They may use medical terminology to further legitimize their explanations [30], which in some situations will be in conflict with their personal experiences [31]. The majority of the participants in the present study had vague and general explanations of their illness, which could indicate that they at the time of interviewing were no longer in a position dominated by intense needs for legitimizing their LBP problems by referring to medical tests and terminology.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research on patients’ experiences of sciatica and its management is scarce [46, 47], especially in those with most severe symptoms, and qualitative studies that report clinicians’ views of managing this condition are even less common [48]. In the SCOPiC trial stratified care arm the ‘fast-track’ pathway to spinal specialist assessment and opinion is novel, and the focus of the qualitative study is on patients in this subgroup and the clinicians involved in their management.…”
Section: Qualitative Studymentioning
confidence: 99%
“…We previously interviewed patients with sciatica and they highlighted its impact, the need for clearer information on treatment and prognosis and patients’ willingness to balance their desire for pain relief with adverse effects [46]. Whilst planning the SCOPiC trial we held a workshop with three patient representatives (who currently had sciatica or had suffered with it in the past) from a research user group.…”
Section: Patient and Public Involvementmentioning
confidence: 99%